(3x+5)+(2x+1)=5(x-1)+9

Simple and best practice solution for (3x+5)+(2x+1)=5(x-1)+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x+5)+(2x+1)=5(x-1)+9 equation:


Simplifying
(3x + 5) + (2x + 1) = 5(x + -1) + 9

Reorder the terms:
(5 + 3x) + (2x + 1) = 5(x + -1) + 9

Remove parenthesis around (5 + 3x)
5 + 3x + (2x + 1) = 5(x + -1) + 9

Reorder the terms:
5 + 3x + (1 + 2x) = 5(x + -1) + 9

Remove parenthesis around (1 + 2x)
5 + 3x + 1 + 2x = 5(x + -1) + 9

Reorder the terms:
5 + 1 + 3x + 2x = 5(x + -1) + 9

Combine like terms: 5 + 1 = 6
6 + 3x + 2x = 5(x + -1) + 9

Combine like terms: 3x + 2x = 5x
6 + 5x = 5(x + -1) + 9

Reorder the terms:
6 + 5x = 5(-1 + x) + 9
6 + 5x = (-1 * 5 + x * 5) + 9
6 + 5x = (-5 + 5x) + 9

Reorder the terms:
6 + 5x = -5 + 9 + 5x

Combine like terms: -5 + 9 = 4
6 + 5x = 4 + 5x

Add '-5x' to each side of the equation.
6 + 5x + -5x = 4 + 5x + -5x

Combine like terms: 5x + -5x = 0
6 + 0 = 4 + 5x + -5x
6 = 4 + 5x + -5x

Combine like terms: 5x + -5x = 0
6 = 4 + 0
6 = 4

Solving
6 = 4

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 9x-9=5x+7 | | 14+(-3)+5+8+(-2)= | | (1+t)sqrt(k)+4k=1 | | 6-(2y-6)=9-3y | | (1+g)sqrt(k)+4k=1 | | 4=3x+5(x+4) | | a-10b/8a-5a-11b/8a | | 5+6r-3=7r+8-3r | | 3(y-7)-8y=4 | | 7y+4=8y | | 0.02/0.7 | | 7(x-9)+6(4x-7)=30(x-4)-3 | | g=3h+5 | | g=4h+1 | | 5.6(4+4x)-9.4=13 | | 4(u+2)-7u=17 | | 0.7/0.02 | | 5/6-(1/18) | | 5.3=x(x+.6)(x-.1) | | 5/8-(1/8) | | 1/5x-3/8y=12 | | 4y+1-2y=3+y+9 | | -4w-2/3=7/5w-4/5 | | -8(n+8)=2-7n | | -10a+40=9 | | X(t)=1-u(t-3)+(t*u(t-3)) | | 8/9x=8+4/9 | | 12a^3/5a | | 6t^2-36t+48= | | 55-8x= | | (X-5)+X=82 | | 3u-25=2u |

Equations solver categories